백서 맹장/복벽 찰과상 모델에서 점도별 HA/CMC 유착 방지 용액의 유효성 및 안정성 평가 - 이윤기(Yun Gee Lee); 추보영(Boyoung Chu); 김남현(Nam Hyun Kim); 김준호(Jun Ho Kim); 이영우(Young Woo Lee); 김광일(Kwang Il Kim); 권성원(Sung Won Kwon) (Annals of surgical treatment and research, 2008)
Purpose: Guardix-solTM is solution type of anti-adhesion barrier, and it is composed of a mixture of hyaluronate (HA) and carboxymethylcellulose (CMC). The anti-adhesive effect was proved through several clinical trials with using this material, but the most efficient viscosity for this solution has not been shown by the previous research. The objective of this study was to evaluate the efficacy and safety of HA/CMC mixture solutions, with varying viscosities, in a rat model. Methods: Three different viscosities (low=LV, mid=MV and high=HV) of the HA/CMC mixture solutions were prepared to evaluate their potential as a tissue adhesion barrier. The viscosity was measured by a Brookfield viscometer. To evaluate the anti-adhesion effect, a cecal-abdominal wall abrasion model was adopted. The denuded cecum was coated by a HA/CMC mixture of different viscosity or it was left uncoated (the negative control group) and then the denuded cecum was apposed to the abdominal wall (each group: n=10). All the rats underwent a second celiotomy after 14 days to evaluate the extent of their abdominal adhesions and tissue reactions (inflammatory response, granulation tissue formation and toxicity in organs). Results: The viscosities of the HA/CMC mixture solutions were 248.±24.4 cps in the LV, 1,353.8±4.4 cps in the MV and 3,556.7±38.8 cps in the HV. The grade of adhesion and the adhesion area were significantly lower in the all HA/CMC mixture solution groups compared to the control regardless of their viscosity. The inflammatory responses were not remarkable at the application site and the major solid organs did not show histological change in the experimental groups. Conclusion: The difference of viscosity of HA/CMC mixture solutions did not affect the efficacy of the adhesion barrier. All the HA/CMC mixture solutions with varying viscosities showed a low inflammatory response and non-toxicity. (J Korean Surg Soc 2008;74:399-404) KCI Citation Count: 4